The Relative Stability of the Dark Triad of Personality - Renaud-da Costa, Audrey (Université d'Ottawa / University of Ottawa, 2025)
The Dark Triad (DT) is a controversial personality profile that includes subclinical traits of psychopathy, Machiavellianism, and narcissism. In recent years, the DT has become a significant concern for social scientists, as its traits are associated with disagreeableness and a socially competitive and dominant interpersonal style. The DT is potentially problematic considering that psychopathy, Machiavellianism, and narcissism are traits, and as such, are supposedly generally stable (i.e., consistent) across time and situations. Nonetheless, personality can change to adapt to, and manifest in, specific situations or moments, known as personality states. Thus, personality is at once, stable and changing over time and in different situations, which is referred to as the relative stability of personality. This relative stability has already been demonstrated with normative traits from the Big Five or Five Factor Model of personality. However, it has rarely been studied with the DT of personality. My doctoral thesis addresses this research caveat by first exploring patterns of stability and change of the DT traits through short time-period (Article 1) and then testing it across situations (Article 2). The results from this doctoral thesis showed greater DT state stability over a ten-day period due to personality traits, despite some state variability due to changes in situations. This was comparable to patterns of relative stability of Big Five Agreeableness. Furthermore, results demonstrated that brief engagement in fictitious social situations did not prompt significant differences in DT states, suggesting that more prolonged and in-depth exposure might be necessary to observe more significant changes in DT states. Overall, these results are aligned with trait theories of personality that consider traits as stable personality attributes.
Keywords: Dark Triad; personality traits vs. states; experimental design; longitudinal design; narcissism; Machiavellianism; psychopathy; relative stability; person-situation debate